Bridging Sacred Values and Modern Demands: A Qualitative Inquiry into Integrated Curriculum Innovation in Islamic Higher Education - Muhamad Abdul Aziz; Imam Mujahid; Usman Abu Bakar (International Journal of Social Sciences, 2026)
This study explores the challenges and strategies in integrating religious values with the modern demands of contemporary society within Islamic higher education institutions. Utilizing a qualitative inquiry approach, this research investigates how curriculum innovation is designed, implemented, and negotiated by academic stakeholders to bridge the gap between sacred traditions and the needs of a globalized market. Data were collected through in-depth interviews with faculty members, curriculum designers, and university administrators, complemented by a thorough analysis of institutional curriculum documents. The findings reveal that curriculum integration is not merely a blending of religious and secular subjects, but a complex process of epistemic reconceptualization. The success of this innovation heavily relies on institutional commitment, the pedagogical readiness of educators, and the flexibility to respond to modern dynamics without compromising spiritual identity. Despite facing hurdles such as ideological resistance and resource limitations, the integrated curriculum innovation proves effective in producing graduates who possess both professional expertise relevant to modern industries and a solid foundation in Islamic ethics. This study offers theoretical contributions to the development of curriculum models in Islamic higher education and provides practical guidance for educational policymakers navigating the dualism of modern and religious education. In conclusion, harmonizing sacred values and modern demands through an integrated curriculum is essential for maintaining the relevance of Islamic higher education institutions in the global era.